"It really proves to us that we are still valuable": Qualitative research to inform a safer conception intervention for men living with HIV in South Africa. - Lynn T Matthews; Letitia Greener; Hazar Khidir; Christina Psaros; Abigail Harrison; F Nzwakie Mosery; Mxolisi Mathenjwa; Kasey O'Neil; Cecilia Milford; Steven A Safren; David R Bangsberg; Jennifer A Smit (PLoS ONE)
Objective Many men living with HIV want to have children. Opportunities to reduce periconception HIV transmission include antiretroviral therapy as prevention, pre-exposure prophylaxis, limiting condomless sex to peak fertility, and sperm processing. Whether men have knowledge of or want to adopt these strategies remains unknown. Methods We conducted focus group discussions (FGDs) with men accessing HIV care in South Africa in 2014 to inform a safer conception intervention for men. Eligible men were 25-45 years old, living with HIV, not yet accessing treatment, and wanting to have a child with an HIV-negative or unknown serostatus female partner (referred to as the "desired pregnancy partner"). FGDs explored motivations for having a healthy baby, feasibility of a clinic-based safer conception intervention, and acceptability of safer conception strategies. Data were analyzed using thematic analysis. Results Twelve participants from three FGDs had a median age of 37 (range 23-45) years, reported a median of 2 (range 1-4) sexual partners, and 1 (range 1-3) desired pregnancy partner(s). A third (N = 4) had disclosed HIV-serostatus to the pregnancy partner. Emergent themes included opportunities for and challenges to engaging men in safer conception services. Opportunities included enthusiasm for a clinic-based safer conception intervention and acceptance of some safer conception strategies. Challenges included poor understanding of safer conception strategies, unfamiliarity with risk reduction [versus "safe" (condoms) and "unsafe" (condomless) sex], mixed acceptability of safer conception strategies, and concerns about disclosing HIV-serostatus to a partner. Conclusions Men living with HIV expressed interest in safer conception and willingness to attend clinic programs. Imprecise prevention counseling messages make it difficult for men to conceptualize risk reduction. Effective safer conception programs should embrace clear language, e.g. undetectable = untransmittable (U = U), and support multiple approaches to serostatus disclosure to pregnancy partners.